Buddy and Earl go exploring - Fergus, Maureen (Buddy and Earl, 2016)
Buddy is just settling in for the night when Earl announces that he's going on a trip. Before buddy knows it, he and Earl are off on another grand adventure. While exploring the wilds of the kitchen, they see wondrous sights, make delicious discoveries and even encounter a couple of unusual monsters.